Counter Radicalization in Cyberspace by the Police - Akbari, Abim Aji; Sagena, Basir; Muhamad Syauqillah (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
This article examines further how the Indonesian police carry out counter-radicalization enforcement in cyberspace. This is important because radicalism triggers a person to be violent towards different views, and this does not follow the nature of the diversity of the Indonesian nation. Radicalism is the embryo of terrorism. This situation becomes more dangerous when radicalization efforts are carried out through cyberspace, which can be accessed by the entire community, including impressionable teenagers. In this regard, the Indonesian National Police, which maintains security and order and protects the community, also takes part in counter-radicalization in cyberspace to ward off negative influences that underlie intolerant and radical actions. This particular observation of the role of the police against radicalism through online media is what then differentiates it from similar research. The discussion uses a qualitative research approach and literature study method, incorporating counter-radicalisation theory through the Internet. This paper finds that counter-radicalization in cyberspace by the police is cyber patrols and content takedown, establishing a social media task force, increasing the role of moderate religious mass organizations, strengthening religious literacy, and collaborating with national and international institutions and digital platforms. In addition, law enforcement is following the ITE Law and the Terrorism Law.